The relationship between unemployment and individual coping: A longitudinal perspective - Maslić Seršić, Darja (Array, 2013)
Employment provides benefits that are critical to well-being. Because of that, employed persons have better mental and physical health than unemployed persons. Also persons who experience prolonged unemployment experience deterioration of physical, social and psychological health. Consequently, their coping resources decrease as well, and it becomes more and more difficult to be re-employed. Reemployment breaks this vicious circle, placing persons in situations where resources for psychosocial growth are accessible again. Given these premises, it is predicted that individual with better coping capacities will be successfully reemployed sooner than individuals with worse and also that prolonged unemployment is followed by decreases, and reemployment by increases in coping resources. In this longitudinal study we examined the coping resources of recently unemployed persons The individual and situational resources assessed in this study were: perceived financial strain, core self-evaluation, social support, and job evaluation. Two waves of data-collection (second wave after 6 months) were conducted with a convenience sample (N=274) of persons who recently became unemployed and who had various demographic and employment profiles. The results of 2x2 repeated-measures ANCOVAs showed different trajectories of coping resources during prolonged unemployment and after re-employment. Perceived social support decreased in both groups during unemployment. Core self-evaluation predicted employment status six months after job loss with its variation during the observed period being moderated by employment status: unemployed individuals showed decreased social support. Level of financial deprivation was a significant predictor of reemployment but did not change during the period and didn’t depend on employment status. Finally, job valuation was not a predictor of reemployment, with intraindividual changes in job valuation during the observed period depending on employment status increased among reemployed individuals and decreased in the still unemployed. The findings of this study will be discussed in light of their implications for psycho-social interventions aimed at supporting successful coping during unemployment and fast re-employment.